Complete chloroplast genome sequence of the rose apple, Syzygium jambos (Myrtaceae). Issue 3 (2nd July 2020) - Sun, Zhixia; Huang, Qingping; Feng, Chen
Abstract: Plants in the genus Syzygium have been widely used as traditional medicine, fruit crops, and ornamental trees. In this study, we reported the complete chloroplast genome of Syzygium jambos (L.) Alston which was known as rose apple. The chloroplast genome of this species is 158541 bp in length, including a pair of inverted repeat regions (IRs) (26076 bp) that is divided by a large single copy area (LSC) (88036 bp) and a small single copy area (SSC) (18353 bp). The circular chloroplast genome of S. jambos contains 132 unique genes, composing of 85 protein-coding genes, 39 tRNA genes and 8 rRNA genes. Phylogenetic analysis indicates that S. jambos is clustered with species in genus Syzygium . This complete chloroplast genome of S. jambos will provide a powerful tool to accelerate breeding, biotechnological and phylogenetic study.